2010
DOI: 10.1080/00958971003674425
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bis(alkylammonium) tetrasulfidometalates

Abstract: The synthesis and characterization of the bis(alkylammonium) tetrasulfidometalates, (EtNH 3 ) 2 [MS 4 ] (M¼ W 1, Mo 2), [BuNH 3 ] 2 [MS 4 ] (M¼ W 3; Mo 4) and (Et-enH 2 )[WS 4 ] 1-en (Et-en ¼ N-ethylethane-1,2-diamine), are reported. Compound 1 crystallizes in the centrosymmetric orthorhombic space group Pnma and its structure consists of discrete slightly distorted tetrahedral [WS 4 ] 2À of m symmetry, separated by two crystallographically independent (EtNH 3 ) þ ions located on mirror planes. The carbons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A systematic study of the alklylammonium heptamolybdates has not been developed except the early work of Yamase [7i] and Roman et al [7h] In our ongoing research program, we have employed organic amines as structure-directing agents and have developed a very rich structural chemistry of organic tetrasulfidomolybdates [MoS 4 ] 2-and the corresponding tetrasulfidotungstates [WS 4 ] 2-. [9] In addition to a general basepromoted cation-exchange reaction for the facile synthesis of group VI tetrasulfidometalates that contain organic ammonium cations, we have shown that the reaction of MoO 3 with aqueous alkylamine followed by treatment with H 2 S gas can be employed for the synthesis of organic [MoS 4 ] 2-compounds. [9a-9g] During the course of our study of alkylammonium tetrasulfidomolybdates, [9a-9d] Figure S1 in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study of the alklylammonium heptamolybdates has not been developed except the early work of Yamase [7i] and Roman et al [7h] In our ongoing research program, we have employed organic amines as structure-directing agents and have developed a very rich structural chemistry of organic tetrasulfidomolybdates [MoS 4 ] 2-and the corresponding tetrasulfidotungstates [WS 4 ] 2-. [9] In addition to a general basepromoted cation-exchange reaction for the facile synthesis of group VI tetrasulfidometalates that contain organic ammonium cations, we have shown that the reaction of MoO 3 with aqueous alkylamine followed by treatment with H 2 S gas can be employed for the synthesis of organic [MoS 4 ] 2-compounds. [9a-9g] During the course of our study of alkylammonium tetrasulfidomolybdates, [9a-9d] Figure S1 in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest works comprise structure elucidation of ammonium sulfidotungstate, [2] followed by the derivatives of the larger alkali metals rubidium, [3] cesium [4] and two closely related modifications of Cu 2 [WS 4 ] [5] as coinage metal representatives. Furthermore, a verified plethora of alkylated and arylated ammonium salts according to (R 1-4 NH 3-0 ) 2 [WS 4 ] (e. g. R = ethyl, butyl, [6] methylbenzyl, [7] etc.) are known as well as sulfidotungstates with mono-and divalent organic cations have been investigated by the group of Srinivasan (e. g. bis(piperazine-1ium) tetrasulfidotungstate, piperazine-diium tetrasulfidotungstate, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Hydrated salts of organic amines exhibit interesting structural features such as a bilayer in 2-aminoanilinium perchlorate monohydrate, 12 sulfate anion helices in ophenylenediammonium sulfate sesquihydrate, 13 a onedimensional polymeric chain of water in [(3-aba) (dabcoH)(H 2 O) 2 ] (3-aba = 3-aminobenzoate; dabco = 1,4-diazabicyclo [2,2,2]octane), 14 a water bridged cyclic dibromide unit in (dbtmen)Br 2 •2H 2 O (dbtmen = N,N′dibenzyl-N,N,N′,N′-tetramethylethylenediammonium), 15 a spiral-like anionic water chain containing a water dimer in (dbtmen)Cl 2 •3H 2 O 16 , water pipe held up by a polyoxometalate supported transition metal complex 17 and linear water dimer in an alkaline earth 4nitrobenzoate. 18 In our research, we have investigated the supramolecular structure of compounds containing tetrahedral anions like tetrasulfidotungstate [19][20][21][22] [WS 4 ] 2− , tetrasulfidomolybdate [23][24][25] [MoS 4 ] 2− , monooxidotrisulfidotungstate 26 [WOS 3 ] 2− , etc. charge balanced by organic ammonium cations.…”
Section: Introductionmentioning
confidence: 99%